2021
DOI: 10.1111/os.13016
|View full text |Cite
|
Sign up to set email alerts
|

Deformed Complex Vertebral Osteotomy Technique for Management of Severe Congenital Spinal Angular Kyphotic Deformity

Abstract: Objectives To (i) introduce the deformed complex vertebral osteotomy (DCVO) technique for the treatment of severe congenital angular spinal kyphosis; (ii) evaluate the sagittal correction efficacy of the DCVO technique; and (iii) discuss the advantages and limitations of the DCVO technique. Methods Multiple malformed vertebrae were considered a malformed complex, and large‐range and angle wedge osteotomy was performed within the complex using the DCVO technique. Patients with local kyphosis greater than 80° wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The hemivertebra was removed with a bone knife and other tools; the use of an ultrasonic bone knife can greatly reduce surgical trauma to soft tissue, especially nervous tissue and vascular tissue. For fully segmented hemivertebrae, the upper or lower endplates and intervertebral discs should be removed 12 . After completion of the osteotomy, the residual cavity was closed until the bone surface was closed, and pre‐shaped correction rods were inserted to complete the correction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hemivertebra was removed with a bone knife and other tools; the use of an ultrasonic bone knife can greatly reduce surgical trauma to soft tissue, especially nervous tissue and vascular tissue. For fully segmented hemivertebrae, the upper or lower endplates and intervertebral discs should be removed 12 . After completion of the osteotomy, the residual cavity was closed until the bone surface was closed, and pre‐shaped correction rods were inserted to complete the correction.…”
Section: Methodsmentioning
confidence: 99%
“…For fully segmented hemivertebrae, the upper or lower endplates and intervertebral discs should be removed. 12 After completion of the osteotomy, the residual cavity was closed until the bone surface was closed, and pre‐shaped correction rods were inserted to complete the correction. The fusion segments were at least two vertebrae above and below the hemivertebra.…”
Section: Methodsmentioning
confidence: 99%
“…These results mirror those of our surgical intervention. Another study [ 27 ] examined twenty-nine patients, and the mean local deformity angle notably improved from 94.9° to 24.0°, with no significant regression during follow-up. There were no instances of intraoperative or neural injury in the perioperative phase.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when compared to PSO and VCR, the following characteristics and benefits of DCVO can be summarized [8][9][10][11][12][13][14][15][16][17][18][19][20]26]: (1) Deformed complex vertebrae usually involve two or more vertebral bodies and the partial or total fusion of many segments' facet joints and intervertebral discs. Multiple deformed and fused vertebrae were treated as a single unit, which simplified complicated problems and aided in developing a more specific osteotomy within the unit and precise positioning during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Deformed complex vertebrae indicated that multiple deformed and fused vertebrae were usually involved with two or more vertebral bodies and the partial or total fusion of many segments' facet joints and intervertebral discs [ 16 ]. The DCVO involves performing a larger posterior wedge-shaped and three-column osteotomy within deformed complex vertebrae using an ultrasonic scalpel, osteotomes, and high-speed drilling to correct a wider range of angles.…”
Section: Methodsmentioning
confidence: 99%